Results of Studying the Sensitivity of S. Pneumoniae Strains Isolated From Patients 2ith Pneumococcal Meningitis to Antibiotics (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The choice of empirical antibacterial therapy (ABT) for community-acquired pneumonia is most dependent on monitoring antibiotic resistance to S. pneumoniae and H. influenza . Today, the spread of isolates among pneumococci with reduced sensitivity to beta- lactam antibiotics, penicillins, third-generation cephalosporins, and the increase in resistance to macrolides is an urgent problem. [ 1,9,15 ]. At the same time, an important element in this issue is the high level of resistance of S.pneumoniae to tetracyclines and cotrimoxazole in pneumococcal isolates isolated from sick children with purulent meningitis and healthy carriers of pneumococcus. [3,5,11]. In recent years, updated data on AMP resistance show an increase in the level of pneumococcal resistance to benzylpenicillin and ampicillin from 6.0 to 14.3% [2,6,10,12]. Resistant strains of S.pneumoniae are most often isolated from elderly patients, when an antibiotic of this group has been used in the next 3 months, recent use of beta- lactam antibiotics, penicillins or co- trimoxazole , HIV infection, as well as in close contact with persons with nasopharyngeal carriage by resistant isolates [8,14].